Weight Loss, Diabetes, Fatigue, and Depression Preceding Pancreatic Cancer. Issue 7 (August 2016) - Olson, Sara H.; Xu, Youming; Herzog, Keri; Saldia, Amethyst; DeFilippis, Ersilia M.; Li, Peter; Allen, Peter J.; O'Reilly, Eileen M.; Kurtz, Robert C.
Abstract : Objectives: We aimed to determine the severity and co-occurrence of established and potential paraneoplastic conditions in pancreatic cancer (weight loss, new onset diabetes, fatigue, and depression) and their relation to patient characteristics. Methods: Using information from personal interviews with 510 cases and 463 controls, we obtained adjusted odds ratios for weight loss, long-term and new-onset diabetes, fatigue, and depression before diagnosis. Among cases, we investigated the extent to which these factors occurred together and the characteristics of those reporting them. Results: The adjusted odds ratio for weight loss (>3% of usual weight) was 27.0 (95% confidence interval, 17.1–42.6). Severe weight loss was common (21% of cases lost >15%), and was more common in those previously obese. Diabetes was more common in cases and was strongly associated with weight loss ( P < 0.0001). Diabetes in cases more often led to prescription of insulin, compared with controls. Fatigue and depression were significantly more common in cases than controls but not related to weight loss or diabetes. These conditions were not related to stage at diagnosis. Conclusions: Weight loss, often severe, and new-onset diabetes frequently occur together before diagnosis of pancreatic cancer. Fatigue and depression are also potential precursors of diagnosis.